DESAIN RISET: PERKEMBANGAN KETERAMPILAN PENGUKURAN SISWA SD MELALUI PERMAINAN PENTENG - Mufarrahatus Syarifah; Heldie Bramantha (CERMIN: Jurnal Penelitian, 2018)
This research is a design research.In implementation, this study includes three stages, namely experimental preparation, design trials, and activity analysis. The design of learning designed in this study aims to develop students' skills in measuring. The designed design involves the traditional game of penteng. Research subjects involved are 3rd grade elementary students. Based on design trials conducted, it is found that through the activity in playing penteng students experience the process directly in the measurement using the measuring tool is not standard. In a penteng game, students measure the distance of the short wood fall to the hole where the wooden throw using long wood and short wood. The experience they get directly when taking measurements using short wood and tracers leads them in declaring distance using the standard unit. This is indicated by the process of counting jumps by students when asked to declare the results of non-standard calculation into the standard unit. Through these activities students' skills in measurement can develop.